2020
DOI: 10.3390/life10010002
|View full text |Cite
|
Sign up to set email alerts
|

Ultradeep Microbial Communities at 4.4 km within Crystalline Bedrock: Implications for Habitability in a Planetary Context

Abstract: The deep bedrock surroundings are an analog for extraterrestrial habitats for life. In this study, we investigated microbial life within anoxic ultradeep boreholes in Precambrian bedrock, including the adaptation to environmental conditions and lifestyle of these organisms. Samples were collected from Pyhäsalmi mine environment in central Finland and from geothermal drilling wells in Otaniemi, Espoo, in southern Finland. Microbial communities inhabiting the up to 4.4 km deep bedrock were characterized with phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 112 publications
0
42
0
Order By: Relevance
“…The subsurface biosphere has unique physical and geochemical conditions that influence the taxa capable of inhabiting this realm. While there is no consensus in the literature thus far on which taxa constitute a typical subsurface biome, locations worldwide suggest the presence of methanogens, sulfate reducers, spore formers, and vast diversity of novel clades including CPR taxa (Chivian et al, 2008;Castelle et al, 2013;Hug et al, 2015;Purkamo et al, 2016;Anantharaman et al, 2016;Lau et al, 2016;Momper, Kiel Reese, et al, 2017;Kadnikov et al, 2017;Probst et al, 2018;Purkamo et al, 2020). Indeed, we see many microbial taxa found previously in subsurface environments including Proteobacteria, Firmicutes, Chloroflexi, Nitrospirae, Archaea, and numerous uncultivated lineages inhabiting DeMMO sites.…”
Section: Ecological Significance To the Subsurface Biospherementioning
confidence: 68%
“…The subsurface biosphere has unique physical and geochemical conditions that influence the taxa capable of inhabiting this realm. While there is no consensus in the literature thus far on which taxa constitute a typical subsurface biome, locations worldwide suggest the presence of methanogens, sulfate reducers, spore formers, and vast diversity of novel clades including CPR taxa (Chivian et al, 2008;Castelle et al, 2013;Hug et al, 2015;Purkamo et al, 2016;Anantharaman et al, 2016;Lau et al, 2016;Momper, Kiel Reese, et al, 2017;Kadnikov et al, 2017;Probst et al, 2018;Purkamo et al, 2020). Indeed, we see many microbial taxa found previously in subsurface environments including Proteobacteria, Firmicutes, Chloroflexi, Nitrospirae, Archaea, and numerous uncultivated lineages inhabiting DeMMO sites.…”
Section: Ecological Significance To the Subsurface Biospherementioning
confidence: 68%
“…Besides more comprehensively studied Bacteria and Archaea, also less abundant Eukaryotes have been shown to be part of the deep biosphere [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Deep subsurface fungi have smaller average cell size compared to known yeasts [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of our experiment are consistent with findings reported by Yang et al [ 2 ], Estendorfer et al [ 39 ], Gu et al [ 68 ], Kumar et al [ 69 ], Gałązka et al [ 70 ], Delgado-Baquerizo et al [ 71 ] and Wemheuer et al [ 72 ]. Microorganisms colonizing the soil environment are responsible for most of the geochemical processes, including nutrient metabolism and energy transfer, whereas the adhesion of microbial cells in the soil, their growth and their development are determined by the granulometric composition of soil; availability of nutrients; and contents of carbon, water, pollutants and substances secreted by plants [ 6 , 7 , 29 ]. The statistical analysis of the data obtained in our study demonstrated that soil pollution with diesel oil significantly stimulated the abundance of all microorganisms tested, whereas the cultivation of Dactylis glomerata enhanced their proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them derive energy from sun rays while others do so from organic and inorganic compounds [ 3 , 4 , 5 ]. This diversity makes them able to convert various pollutants [ 6 ], including those contained in petroleum-based products [ 7 ], which consequently affects the succession of microorganisms in the natural environment [ 6 , 8 ]. Hydrocarbons [ 7 , 9 , 10 , 11 ], heavy metals [ 12 , 13 , 14 , 15 ] and pesticides [ 16 , 17 ] are a severe threat to the natural environment due to their high accumulation potential and high toxicity in the soil ecosystem [ 18 ].…”
Section: Introductionmentioning
confidence: 99%